A semi-automated method for counting fluorescent malaria oocysts increases the throughput of transmission blocking studies - Delves, M; Sinden, R; Sinden, R (BioMed Central, 2010)
Background. Malaria transmission is now recognized as a key target for intervention. Evaluation of the Plasmodium oocyst burden in the midguts of Anopheles spp. is important for many of assays investigating transmission. However, current assays are very time-consuming, manually demanding and patently subject to observer-observer variation. Methods. This report presents the development of a method to rapidly, accurately and consistently determine oocyst burdens on mosquito midguts using GFP-expressing Plasmodium berghei and a custom-written macro for ImageJ. The counting macro was optimized and found to be fit-for-purpose by performing gametocyte membrane feeds with parasite infected blood. Dissected midguts were counted both manually and using the automated macro, then compared. The optimized settings for the macro were then validated by using it to determine the transmission blocking efficacies of two anti-malarial compounds - dehydroepiandrosterone sulphate and lumefantrine, in comparison to manually determined analysis of the same experiment. Results. Concurrence of manual and macro counts was very high (R2 = 0.973) and reproducible. Estimated transmission blocking efficacies between manual and automated analysis were highly concordant, indicating that dehydroepiandrosterone sulphate has little or no transmission blocking potential, whilst lumefantrine strongly inhibits sporogony. Conclusion. Recognizing a potential five-fold increase in throughput, the resulting reduction in personnel costs, and the absence of inter-operator/laboratory variation possible with this approach, this counting macro may be a benefit to the malaria community. © 2010 Delves and Sinden; licensee BioMed Central Ltd.